An investigation of how to address climate change-induced land degradation in Balaka, Malawi, by reconciling indigenous and scientific knowledge - Chamasula, Victoria; Rabumbulu, Mulalo (Frontiers in Human Dynamics, 2024)
Malawi, like the majority of African countries, is experiencing land degradation as a result of climate change and unsustainable farming methods. Land degradation is a worldwide problem, but Africa is the worst affected, with 75% of arable land already degraded. Malawi is primarily an agricultural country, with 11 million people practicing small-scale subsistence farming. Given the hilly terrain, forests, and tough pastures, only one-third of the county is considered cultivable. However, agriculture accounts for 30% of Malawi’s GDP, exporting 80% of its agricultural produce. Small-scale farmers are essential producers, farming 5.3 million hectares of land and accounting for over 70% of Malawi’s food consumption. Unfortunately, as climate change and economic demands increase, so does land degradation. Even though indigenous knowledge has been used for generations to adapt to changing environments, there is an unmistakable distinction between scientific and indigenous knowledge, with scientific being seen as far superior. Several studies have revealed that depending entirely on one knowledge system is insufficient for effectively addressing environmental concerns. Thus, there is a need for more comparisons that allow for a complementary application of the two knowledge systems rather than their contradiction. In this work, we identify indigenous indicators of land degradation and land management practices utilized by Malawian farmers, and we investigate how indigenous and scientific knowledge systems might be combined to adapt and address the issue of land degradation swiftly. To do this, 100 semi-structured interviews were conducted with farmers in five villages. Atlas-ti software was used to do thematic content analysis on the dataset. Our findings show farmers’ coping techniques are still based on IK and motivated by experiential learning from earlier climatic crises. Though most farmers know scientific land management practices, current adaption strategies rely on expensive resources and are inappropriate for indigenous farmers. The study investigates various ways scientific and indigenous knowledge could be integrated to enhance climate change adaptation against land degradation. These encompass developing indigenous indicator baselines, including new measures for measuring soil fertility, and more effective and energy-efficient irrigation technologies.